Gene expression dynamics in Bacillus cereus and Bacillus subtilis treated with Thymus vulgaris and Origanum vulgare subsp. hirtum essential oils - Anniballi, Fabrizio; Purgatorio, Chiara; Serio, Annalisa; Scalfaro, Concetta; Taglieri, Silvia; Paparella, Antonello (Frontiers in Microbiology, 2025)
Essential oils (EOs) hold significant potential as antimicrobials in food, due to their high concentration of active phenolic compounds. These compounds can target bacterial cells through various mechanisms, such as membrane disruption, quorum sensing inhibition, and interference in virulence factors, affecting microorganisms at a genomic level. Bacillus cereus and Bacillus subtilis are key foodborne bacteria that could be managed using these natural preservatives. The present study investigated the effects of stress induced by applying Thymus vulgaris and Origanum vulgare subsp. hirtum EOs on genetic modifications in B. cereus 11 and B. subtilis 58C strains isolated from shelf-stable gnocchi, through their gene expression analysis by quantitative real-time RT-PCR. Sublethal EO concentrations were tested, at increasing time intervals (6, 12, 18, 24, and 48 h). Most of the genes were downregulated at 6 h, indicating that the stressful situation prolonged the lag phase. Only spo0A for both B. cereus and B. subtilis, and pbpF and sigB for B. subtilis were upregulated after 6 h, suggesting an attempt to restore cellular communication and repair membrane damage. The pbpF gene was the most significant in the stress response of B. subtilis. Conversely, B. cereus responded through different mechanisms, primarily driven by the plcR and nheB genes, illustrating the role of virulence mechanisms in its stress response. In both strains, the genes were generally more upregulated at a higher concentration of EO (0.58 mg/mL), which was more stimulating than at 0.29 mg/mL. Moreover, the two EOs elicited variable stress responses, which implies different cellular mechanisms and genes in the same microorganism. Therefore, the outcomes of this study suggest that the action of the two EOs mainly influenced cell membrane integrity and quorum sensing mechanisms, with differences in the genes involved for the two species and the two EOs.